2015
DOI: 10.1186/s12977-015-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of CD4+ T cells from elderly individuals to HIV-1 infection and apoptosis is associated with reduced CD4 and enhanced CXCR4 and FAS surface expression levels

Abstract: BackgroundElderly HIV-1 infected individuals progress to AIDS more frequently and rapidly than people becoming infected at a young age. To identify possible reasons for these differences in clinical progression, we performed comprehensive phenotypic analyses of CD4+ T cells from uninfected young and elderly individuals, and examined their susceptibility to HIV-1 infection and programmed death.ResultsPeripheral blood mononuclear cells (PBMCs) from older people contain an increased percentage of central memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Notably, in this current study, we did not observe differences in expression of CTLA-4 or PD-1 between younger and older memory PB CD4 T cells (albeit from unmatched donor blood samples), potentially highlighting a gut-specific effect. Although previous studies have noted an age-associated increase in CTLA-4 or PD-1 expression on blood CD4 T cells [ 26 29 ], the lack of an apparent age effect observed here is in agreement with a number of other studies [ 30 33 ] and may relate to study populations (e.g. age range, sex) and/or the type of CD4 T cell evaluated (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, in this current study, we did not observe differences in expression of CTLA-4 or PD-1 between younger and older memory PB CD4 T cells (albeit from unmatched donor blood samples), potentially highlighting a gut-specific effect. Although previous studies have noted an age-associated increase in CTLA-4 or PD-1 expression on blood CD4 T cells [ 26 29 ], the lack of an apparent age effect observed here is in agreement with a number of other studies [ 30 33 ] and may relate to study populations (e.g. age range, sex) and/or the type of CD4 T cell evaluated (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…CCR5-tropic viruses predominate most isolates from human bodies globally and usually found in the early HIV infection. CXCR4-tropic viruses are fewer, and usually found in the late stage of infection [ 4 , 9 , 10 ]. CCR5 delta 32 mutation is a deletion of 32 base pairs after amino acid position 185, resulting in a premature and non-functional CCR5 receptor [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CD4 T cells from C. trachomatis-infected patients and healthy donors showed no significant difference in the expression levels of CD4 activation markers CD69 and HLA-DR J o u r n a l P r e -p r o o f 12 as well as CCR5 coreceptor. These results suggested that the enhanced susceptibility or infectivity was probably due to other factors other than increased expression levels of CD4 activation markers (Heigele et al, 2015, Rubbo et al, 2011.…”
Section: Discussionmentioning
confidence: 92%